Long-term analysis of humoral responses and spike-specific T cell memory to Omicron variants after different COVID-19 vaccine regimens - Ho, Chia-Lo; Yen, Li-Chen; Huang, Hong-Wei; Lu, Chun-Chi; Hung, Yi-Jen; Liao, Ching-Len; Hung, Chin-Mao; Chiu, Kuo-Chou (Frontiers in Immunology, 2024)
Background The emergence of SARS-CoV-2 variants has raised concerns about the sustainability of vaccine-induced immunity. Little is known about the long-term humoral responses and spike-specific T cell memory to Omicron variants, with specific attention to BA.4/5, BQ.1.1, and XBB.1. Methods We assessed immune responses in 50 uninfected individuals who received varying three-dose vaccination combinations (2X AstraZeneca + 1X Moderna, 1X AstraZeneca + 2X Moderna, and 3X Moderna) against wild-type (WT) and Omicron variants at eight months post-vaccination. The serum antibody titers were analyzed by enzyme-linked immunosorbent assays (ELISA), and neutralizing activities were examined by pseudovirus and infectious SARS-CoV-2 neutralization assays. T cell reactivities and their memory phenotypes were determined by flow cytometry. Results We found that RBD-specific antibody titers, neutralizing activities, and CD4+ T cell reactivities were reduced against Omicron variants compared to WT. In contrast, CD8+ T cell responses, central memory, effector memory, and CD45RA+ effector memory T cells remained unaffected upon stimulation with the Omicron peptide pool. Notably, CD4+ effector memory T cells even exhibited a higher proportion of reactivity against Omicron variants. Furthermore, participants who received three doses of the Moderna showed a more robust response regarding neutralization and CD8+ T cell reactions than other three-dose vaccination groups. Conclusion Reduction of humoral and CD4+ T cell responses against Omicron variants in vaccinees suggested that vaccine effectiveness after eight months may not have sufficient protection against the new emerging variants, which provides valuable information for future vaccination strategies such as receiving BA.4/5 or XBB.1-based bivalent vaccines.